An analysis of glaucoma repeat measures assessment results: Are core competencies enough?. (20th August 2022) - Karas, Marek; Bartlett, Sophie; Whitaker, Angela; Sheen, Nik; North, Rachel; Ryan, Barbara
Abstract: Purpose: The need to validate core competency skills in qualified optometrists wishing to take part in extended roles in glaucoma care has been questioned. This analysis examines the ability of qualified optometrists to perform relevant core competency skills under standardised objective assessment conditions to explore whether such validation is justified. It also investigates if there are associations between performance, gender and length of time since qualification. Methods: Anonymised data from the Cardiff University assessment programme for the Wales Optometry Postgraduate Education Centre (WOPEC) Local Optical Committee Support Unit glaucoma referral filtering and monitoring pathway delivered between January 2017 and March 2020 were analysed. Results were combined with demographic data from the General Optical Council register of optometrists in the UK to investigate associations between performance and practitioner characteristics, namely length of time since qualification and gender. Results: The assessment results of 2215 optometrists practising in England (approximately 15% of all UK registered optometrists and 30% of all optometrists registered in England) were analysed. Failure rates for first time assessment in each of five objective structured clinical examination style practical assessments were 8.5% (van Herick); 8.8% (slit lamp binocular indirect ophthalmoscopy); 10.1% (Goldmann applanation tonometry calibration); 21.9% (Goldmann applanation tonometry) and 23.3% (case scenario interpretation and management). There were either no associations or at most very weak associations between performance and practitioner characteristics. Conclusions: Our results suggest that these competencies are not universally present in optometrists practising in England and that ongoing training and assessment of these competencies is justified for entry into extended roles. There are no meaningful associations between performance in these assessments and gender or time since qualification.